No evidence for long‐term effects of reproductive effort on parasite prevalence in great tits Parus major. (31st January 2014) - de Jong, Margje E.; Fokkema, Rienk W.; Ubels, Richard; van der Velde, Marco; Tinbergen, Joost M.
<x xml:space="preserve">Abstract</x> Allocation of resources between the life history traits reproduction and parasite defence are expected because both are energetically costly. Experimental evidence for such allocation has been found in short‐term effects of reproduction on parasite prevalence or immune function. However, there is increasing evidence for long‐term negative effects of reproductive effort on individuals. This study investigates whether long‐term effects of reproductive effort on parasite prevalence exist. Brood sizes of great tits Parus major were experimentally altered in one breeding season and in the subsequent breeding season the prevalence of three parasites types (blood parasites, ticks and fleas) on the surviving parents were investigated. We detected no long‐term effects of brood size manipulation on the prevalence of parasites in the next year and therefore provide no evidence for inter‐seasonal effects of reproductive effort on parasite prevalence. The post hoc level of statistical power was reasonable for effects on blood parasite and flea prevalence, but low for effects on tick prevalence.